Translating and (re)constructing the self in a different language: exploring the language memoirs "Lost in translation" by Eva Hoffman and "Heading south, looking north" by Ariel Dorman - Meisch, Sarah (My University, 2011)
This thesis investigates the trope of ‘lost in translation’ with regard to immersion in another language and aims to show that the notion requires revisiting in order to test the validity of the contention of irretrievable loss and lack in self-translation. Exploring the language memoirs Lost in Translation by Eva Hoffman and Heading South, Looking North by Ariel Dorfman, the research shows that whilst there is indeed substantial loss, disorientation and estrangement involved in transferring the self into another language and culture, valuable gains and positive personal growth nevertheless emerge. Primarily the thesis examines how, due to the role of language and culture in the formation of the self, the process entails translation and (re)construction of the self, which inevitably involves modification. In language memoirs the inherent properties of autobiographical writing add another dimension to this translation. In this way, given the multifaceted and fluid nature of identity, the process of self-translation attests to the potential limitlessness of identity and is presented as a heightened version of standard identity dilemmas and the lifelong construction of the self. In the knowledge of their complexity and the need for continual revision of the self, Hoffman and Dorfman recognise the misplaced nostalgia for a fixed and cohesive self, and embrace the wider access to identity options and means of expression that living with more than one language allows them. Enhanced self-consciousness, expanded perspectives and further aspects of the self that are revealed in the new language lead to personal growth as well as fuel creativity, serving as an impetus for writing. These authors are therefore not only ‘lost in translation’ but also ‘found’ and principally ‘altered’. The notion of ‘lost in translation’ is thus established as insufficient in describing the experience of the self in language memoirs, and the rewriting of the self in another language rather necessitates a theory of overriding transformation that acknowledges both losses and gains. Translation of the self thus unfolds as a metamorphosis that does not replace one self with another but instead embraces aspects of both languages and constructs a palimpsest-like interlayering of a multidimensional identity.
Ph.D. Faculty of Humanities, University of the Witwatersrand, 2011